Experimental and Numerical Study on Modal Dynamic Response of Water-Surrounded Slender Bridge Pier with Pile Foundation - Yulin Deng; Qingkang Guo; Lueqin Xu (Shock and Vibration)
This paper presents an experimental program performed to study the effect of fluid-structure interaction on the modal dynamic response of water-surrounded slender bridge pier with pile foundation. A reduced scale slender bridge pier specimen is built and tested through forced vibration method. The vibration periods of the first four lateral modes, including the first two modes along x-axis and the first two modes along y-axis, are measured based on the specimen submerged by 16 levels of water and designated with 4 levels of tip mass. Three-dimensional (3D) finite-element models are established for the tested water-pier system and analyzed under various combined cases of water level and tip mass. Percentage increases of vibration periods with respect to dry vibration periods (i.e., vibration periods of the specimen without water) are determined as a function of water level and tip mass to evaluate the effect of fluid-structure interaction. The numerical results are successfully validated against the recorded test data. Based on the validated models, the modal hydrodynamic pressures are calculated to characterize the 3D distribution of hydrodynamic loads on the pier systems. The research provides a better illumination into the effect of fluid-structure interaction on the modal dynamic response of deepwater bridges.